Forensic linguistics in German law enforcement - Ehrhardt, Sabine (Language and Law / Linguagem e Direito, 2021)
In Germany, forensic linguistics is regularly made use of for law enforcement purposes. Since the 1980s, it is part of a federal forensic science institute and has developed with other, more widely-known forensic sciences side by side. Its contributions are fully accepted by the German police and the courts. To illustrate the processes surrounding expert evidence in German jurisprudence, the forensic linguistic expert work on a homicide case will be outlined at its various stages, i.e. from investigation up to the confirmation of the judgement after an appeal to the Federal Court of Justice. Tracing the course of the case, general provisions (legal or otherwise) concerning each stage of law enforcement are outlined and it will be described how they apply to forensic linguistics. Special attention is paid to the role of the expert, the expert’s rights and responsibilities, and what can be learned from the feedback of court proceedings